2023
DOI: 10.3390/jcm12113753
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dual-Acquisition Noninvasive Cardiac CT Imaging for the Detection of Vasospastic Angina

Abstract: Background: Vasospastic angina (VSA) is characterized by chest pain at rest with transient ischemic electrocardiographic changes in the ST segment, and a prompt response to nitrates. Vasospastic angina is among the most frequent of the coronary artery diseases in Asia, and coronary computed tomography angiography (CCTA) may become available as a non-invasive diagnosis method. Methods: We prospectively enrolled 100 patients with suspected vasospastic angina at two centers from 2018 to 2020. All patients underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…A large study using ergonovine stress echocardiography found 43% of wall motion abnormalities to be in the LAD region [22]. Jin et al reported a higher frequency of positive coronary spasms for the LAD (64.3%) in probable positive definition and the RCA (65.4%) in positive definition, albeit in a few cases [23]. In our study, the frequency of coronary spasms in the LAD was clearly higher.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…A large study using ergonovine stress echocardiography found 43% of wall motion abnormalities to be in the LAD region [22]. Jin et al reported a higher frequency of positive coronary spasms for the LAD (64.3%) in probable positive definition and the RCA (65.4%) in positive definition, albeit in a few cases [23]. In our study, the frequency of coronary spasms in the LAD was clearly higher.…”
Section: Discussionsupporting
confidence: 43%
“…In any case, if the involvement of the LCX Life 2023, 13, 2072 9 of 12 in coronary spasms is to be clarified, the SPT may be started from the LCA. Furthermore, the frequency of coronary spasms in the LAD and RCA also varied between reports [21][22][23]; Sueda et al [21] reported no difference in the positivity rate between the RCA (73.3%) and LAD (72%). A large study using ergonovine stress echocardiography found 43% of wall motion abnormalities to be in the LAD region [22].…”
Section: Discussionmentioning
confidence: 98%